Створення леґенди про Совія в «Іудейському хронографі» другої половини ХІІІ ст. - Вілкул, Т.Л. (Український історичний журнал, 2012)
Чимало свідчень про язичницьке минуле в давньоруських літописах і хронографах
пов’язані з перекладними грецькими пам’ятками. Уміщена в «Іудейському хронографі» другої половини XIII ст. леґенда про Совія, яка оповідає про звичаї дохристиянської
Литви, у цьому сенсі не становить винятку. Судячи з усього, Совій та весь епізод про
язичницькі литовські звичаї з’явився завдяки переосмисленню укладачем хронографа
декількох текстів: фраґментів хронік Георгія Амартола та Іоанна Малали, Книги
Буття й «Збірника 16 слів» Григорія Богослова з коментарями Нікіти Іраклійського. A great deal of reminiscences of the pagan past that can be found in the Old Rus’ chronicles
and chronographs, are deeply indebted to the translations of the earlier Greek authors. In
this respect the legend of Sovii relating Lithuanian pagan customs is no exception to the
rule. This legend was first written down in the “Jewish Chronicle” (“Judea Chronograph”),
which was composed in the second half of the XIIIth century. It is argued that the legendary
Sovii resulted from a bookman’s reflection on a number of texts, namely: the fragments of
the chronicles of George Hamartolus and John Malalas; Genesis; the collection of 16 Words
by Gregory of Nazianzen with commentaries by Nicetas of Heraclea.